Repo markets and the financial crisis - Samuel, Teresa Esther Louise Alwine (2018)
Bank runs on short term debt can lead to financial crises with short term debt being constituted in different forms. While the Great Depression in the 1930’s was shaped by a run on bank deposits, markets for repurchase agreements (repo markets) were in the center of the 2008 financial crisis. Given that repo markets provide liquidity in interbank markets and represent the main source of funding for securitized banking activities, this paper analyzes the institutional background of repos and puts them in a quantitative context using financial data. I provide evidence that changes in repo markets during the financial crisis had a similar impact on the economy as the withdrawal of bank deposits during the Great Depression.